PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH - Putu Satya Purnama Sari; Ni Made Wisni Arie Pramuki (Hita Akuntansi dan Keuangan, 2021)
The purpose of this research is to obtain empirical evidence of the influence of human capital, structural capital, and customer capital on performance of small and medium business (SMEs) in Tampaksiring. This research is quantitative research, using primary data through questionnaires and measured using likert scale. The sampling technique used simple random sampling technique. The samples used in this study were 125 SMEs in Tampaksiring. The data analysis method used is the Smart PLS 3.0 program. The result showed that structural capitals have a positive and significant effect on performance of SMEs. While the human capital and customer capital has positive no significant effect on performance of SMEs.